Environmental Stress Affects the Formation of Staphylococcus aureus Persisters Tolerant to Antibiotics - Kubistova, Lucie; Dvoracek, Lukas; Tkadlec, Jan; Melter, Oto; Licha, Irena (Microbial drug resistance, 2018)
The ability to form persisters has been observed in many microorganisms, including Staphylococcus aureus, mainly in the context of chronic infections and the pathogenicity of these microbes. In our research, we have demonstrated that salt or oxidative stress could play a role in the formation of S. aureus persisters outside the host's intracellular interface. We pre-exposed planktonic growing bacterial culture to an oxidative or salt stress and monitored the dynamics of persister formation after ciprofloxacin and gentamicin treatment. In parallel, using the quantitative PCR (qPCR) approach, we determined the expression level of the stress sigma factor SigB. The pre-exposure of bacteria to salt stress caused a 1-2.5 order of magnitude increase in persister formation in the bacterial population after antibiotic exposure, depending on the type and concentration of the antibiotic used. In contrast, oxidative stress only minimally influenced the formation of persisters, without correlation to the antibiotic type and concentration. We have demonstrated that both stress and antibiotic exposure increase the expression of sigB in bacterial populations from very early on. And that the expression level of sigB differs with the type of antibiotic and stress, but no correlation was observed between persister formation and sigB expression. The method used could be helpful in testing the ability that strains can have, to form persisters.
Keywords: stafylokokové infekce; antibakteriální látky; Staphylococcal Infections; Anti-Bacterial Agents; bakteriální geny; fyziologický stres; Stress, Physiological; Genes, Bacterial; Staphylococcus aureus